Ice sports - Barrett, Norman S.; Burns, Rhoda; Burns, Robert (New York : F. Watts, 1988)
An introduction, in brief text and illustrations, to the history and technique of various kinds of ice sports.
Includes index.
Booklist.
5.2
3-6
Keywords: Skating -- Juvenile literature; Winter sports -- Juvenile literature; Ice skating; Winter sports; Winter sports